About standardization of L-lysinum 3-methyl-1,2,4-thiazolyl-5-thioacetate tablet mass - O. S. Bidnenko; L. I. Kucherenko; I. A. Mazur; G. I. Tkachenko (Zaporozhye State Medical University, 2016)
Aim. These days despite the constant efforts to optimize treatment of CNS and cardio - vascular system diseases the problem still remains unsolved. Taking into consideration the rising cost of medical care and accompanying social problems the development and launching of new approaches, methods and treatment regimens to increase clinical effectiveness of therapy are actual. L-lysinum-3-methyl-1,2,4-thiazolyl-5-thioacetate is the representative of metabolite drugs with marked effect on the endothelium of the brain and heart blood vessels. Cardioprotective properties of the medication are aimed to ameliorate the persistence of cardiomyocytes during acute myocardial ischemia and to improve the ECG measurements. It is well known that medications for the cardiovascular disease treatment in most cases should be used during a long time period, and even lifelong. Therefore, rational drug dosage form - tablet - has been chosen for new drug. It is also known that great attention in the production of tablets is paid to stepwise quality control. Methods and results. Therefore, the purpose of our study was the development of standardization methods of L-lysinum-3-methyl-1,2,4-triazolyl-5-thioacetatе in the tablet mass by spectrophotometry. During the work 6 series of L-lysinum-3-methyl-1,2,4-triazolyl-5-thioacetate tablet mass were studied. Conclusions. Thus, we established that all series meet the requirements of the State Pharmacopeia of Ukraine concerning the content of the active substance. Our research resulted in the development of a sensitive, objective, reliable and reproducible method of the spectrophotometric determination of L-lysinum-3-methyl-1,2,4-triazolyl-5-thioacetate in the tablet mass.